Tarbiyah analysis in life: Historical approach and curriculum development - Mohamad Agung Rokhimawan; Istiningsih Istiningsih (Journal of Education and Learning (EduLearn), 2019)
The findings of the research are the tarbiyah curriculum journey grouped into eight stages of curriculum development. Starting from the embryo curriculum in 1961, this is the first stage as a curriculum based on the main points of the Pancasila Education System. The second stage of the curriculum, which contains prioritising the mastery of science and technology, has not been focused on formulating its abilities. In the third stage, the paradigm shift to the concept of competency-based curriculum. The college itself developed the fourth stage of the curriculum. The fifth stage is the university curriculum is developed and implemented based on competency for each study program. Sixth, the curriculum of learning achievement is adjusted to the level of KKNI. The seventh stage, the competence of graduates, is determined by referring to KKNI. In the eighth stage, the higher education curriculum contains an equal quality of learning outcomes. Find curriculum design concepts for tarbiyah in the future. Where the eight components of the curriculum concept are Competence Achievement, Continuous Improvement, Functional for users, Adaptable to the social community, Sharing on core values of UIN, Build real scientist. This is all to answer the challenges of developing the tarbiyah curriculum in the future.